Gallic acid protects against cadmium chloride-induced alterations in Wistar rats via the antioxidant defense mechanism - Oluwafemi Adeleke Ojo; Damilare Rotimi; Ayomide Emmanuel Bright; Omowumi Titilola Kayode; Adebola Busola Ojo; Omokolade Oluwaseyi Alejolowo; Basiru Olaitan Ajiboye; Olarewaju M. Oluba (GarVal Editorial Ltda., 2021)
Context: Cadmium has been considered as one of the most hazardous toxic compounds with harmfully effect on the health of organisms. Aims: To evaluate the effects of gallic acid (GA) on the cadmium-induced liver and renal oxidative stress in Wistar rats. Methods: Twenty Wistar rats were grouped into four (A-D) of five rats. Rats in Group A, B, C and D were administered distilled water, 5 mg/kg bw cadmium chloride (CdCl2), CdCl2 + GA concurrently and GA (20 mg/kg bw) respectively and administered for 14 days. Biochemical parameters such as antioxidant enzyme activities, urea, creatinine and myeloperoxidase activity were determined. Results: In the urea, creatinine and MPO, there was a significant increase in the CdCl2 treated group. In the liver, the CdCl2 treated group reduced significantly the catalase activity and increased the reduced glutathione. The gallic acid group increased in the GSH level, SOD, and CAT activities and it also reduced significantly the MDA level. However, the co-administration of CdCl2 + GA had a considerably increase in the antioxidant enzymes. In the kidney, catalase activity and MDA level significantly decrease and increase respectively. The gallic acid also increases significantly the CAT and SOD activities while the MDA level was reduced. Co-administration of GA + CdCl2 had a substantial increase only in the SOD activity compared to the control. Conclusions: This study indicates that gallic acid was able to protect the alteration induced by cadmium chloride in the rat kidney and liver.